2014
DOI: 10.1016/j.tiv.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects between electronic and cigarette smoke in human keratinocytes and epithelial lung cells

Abstract: Background Information about the harmful effects of vaping is sparse and inconsistent, therefore, since the use of electronic cigarettes (e-CIGs) has become increasingly popular as a tool to limit tobacco smoking, it is urgent to establish the safety or the toxicity of the liquid vaporized by the atomizer of the commercial e-CIGs. Methods Skin (HaCaT) and lung (A549) cells, the main targets of cigarette smoke, were exposed to e-CIG vapor (e-CIG Mini Touch T-Fumo T-TEX) and cigarette smoke (UK research cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
3
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 17 publications
9
147
3
12
Order By: Relevance
“…concluded that nicotine concentration had no effect on myocardial cell survival when comparing different ECEs, and Bahl et al (2012) reported that cells did not survive better in samples without nicotine when subjected to direct e-liquid exposure. Cervellati (2014) however, showed that nicotine did have an effect on the viability and inflammatory response of cells exposed to EC vapour, though this was not using ECE.…”
Section: The Effect Of Nicotine Concentrationmentioning
confidence: 94%
“…concluded that nicotine concentration had no effect on myocardial cell survival when comparing different ECEs, and Bahl et al (2012) reported that cells did not survive better in samples without nicotine when subjected to direct e-liquid exposure. Cervellati (2014) however, showed that nicotine did have an effect on the viability and inflammatory response of cells exposed to EC vapour, though this was not using ECE.…”
Section: The Effect Of Nicotine Concentrationmentioning
confidence: 94%
“…E‐cigarettes cause toxicity to NHBE48 and A549 airway and lung cells via oxidative stress (Cervellati et al. 2014; Scheffler et al. 2015), and both nicotine free and nicotine‐containing E‐cigarette vapor caused loss of lung endothelial barrier function (Schweitzer et al.…”
Section: Introductionmentioning
confidence: 99%
“…The conducted tests proved that it is not the case. For the first time it has been shown that exposure to e-cigarette vapour free of flavour results in the release of the following cytokines and chemokines: PDGF-BB, FGF, IL-8, IL-12, IL-17, GM-CSF, IP-10, MCP-1 and MIP-1b [16]. It has not been observed that short-term use of e-cigarettes leads to increased concentration of IL-2, TNF-a, EGF, whose growth was noticed directly after consumption of a regular cigarette [17].…”
Section: The Chemical Composition Of Electronic Cigarettes Their Toxmentioning
confidence: 99%